Bridging Young Learners’ English Proficiency through Interactive Educational Games at SDN Ciheuleut 2, Bogor City - Bonanza, Occy; Abikusno, Rhino; Resmayasari, Ira; Fami, Amata; Barus, Irma Rasita Gloria; Wahyoedi, Bontisesari (Asian Journal of Community Services, 2024)
This report investigates the integration of interactive educational games aimed at enhancing English language learning in elementary level. Conducted at SDN Ciheuleut 2 in Bogor City, the study focused on three games—"Shout Out Loud," "Guess the Animal," and "Stack the Blocks"—specifically designed for vocabulary and language development. Employing pre-test/post-test assessments, the study aimed to uncover their impact on student proficiency levels. The results showed an increase in students’ test scores following the integration of these games, showing a 20.65% rise in overall test scores. Classroom observations also noted heightened student enthusiasm during class activities. These findings highlight the positive relationship between educational games and students’ language development, establishing an engaging learning atmosphere crucial for young learners' language acquisition.